Longitudinal anti-SARS-CoV-2 antibody immune response in acute and convalescent patients - Pérez-Juárez, Horacio; Serrano-Vázquez, Angélica; Godínez-Alvarez, Héctor; González, Enrique; Rojas-Velázquez, Liliana; Moran, Patricia; Portillo-Bobadilla, Tobías; Ramiro, Manuel; Hernández, Eric; Lau, Clara; Martínez, Marcela; Padilla, Ma. de los Ángeles; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Despite global efforts to assess the early response and persistence of SARS-CoV-2 antibodies in patients infected with or recovered from COVID-19, our understanding of the factors affecting its dynamics remains limited. This work aimed to evaluate the early and convalescent immunity of outpatients infected with SARS-CoV-2 and to determine the factors that affect the dynamics and persistence of the IgM and IgG antibody response. Seropositivity of volunteers from Mexico City and the State of Mexico, Mexico, was evaluated by ELISA using the recombinant receptor-binding domain (RBD) of the SARS-CoV-2 Spike protein for 90 days, at different time points (1, 15, 45, 60, and 90 days) after molecular diagnosis (RT-qPCR). Gender, age range, body mass index (BMI), comorbidities, and clinical spectrum of disease were analyzed to determine associations with the dynamics of anti-SARS-CoV-2 antibodies. On 90 days post-infection, individuals with moderate and asymptomatic disease presented the lowest levels of IgM, while for IgG, at the same time, the highest levels occurred with mild and moderate disease. The IgM and IgG levels were related to the clinical spectrum of disease, BMI, and the presence/absence of comorbidities through regression trees. The results suggest that the dynamics of anti-SARS-CoV-2 IgM and IgG antibodies in outpatients could be influenced by the clinical spectrum of the disease. In addition, the persistence of antibodies against SARS-CoV-2 could be related to the clinical spectrum of the disease, BMI, and the presence/absence of comorbidities.